The new world - Horner, James 1953-2015 (New Line Home Entertainment, 2008)
Captain John Smith leaves the Jamestown fort to explore and trade with the Indians, but he is captured. Princess Pocahontas asks her father to spare Smith's life and they fall in love. When he returns to Jamestown, he finds the people starving. Pocahontas brings supplies, but while saving them English, she falls in disgrace with her people. When the Indians realize that the English will not leave their country, they attack. After a bloody battle, the English trade Pocahontas and lodge her in the fort to protect their families. With the return of Captain Newport, Smith is promoted and sent back to England. He asks a friend to tell Pocahontas that he drowned during the trip. Pocahontas is civilized and baptized by the English and John Rolfe proposes and marries her. Many years later, she hears that Captain Smith is alive, and she has to decide if she keeps her marriage or follows her heart